Do You Feel Included? A Latent Profile Analysis of Inclusion in the Chinese Context - Qu, Jiaojiao; Wang, Mengcheng (Frontiers in Psychology, 2022)
Although the importance of inclusion has been firmly supported by prior studies, the question of whether certain subgroups exist in the workplace whose members feel more or less included remains under-explored, limiting our understanding of how an inclusive workplace can be achieved. To address this gap, the current study conducted a latent profile analysis (LPA) to obtain evidence-based information regarding employees’ sense of inclusion in their organizations. Using a sample of 1,168 participants engaged in multiple industries in China, we identified three profiles of inclusion, with a largest proportion feeling a moderate level of inclusion (69.5%), a smaller proportion feeling a high level of inclusion (22.7%), and a tiny proportion feeling a low level of inclusion (7.8%). The three profiles differ significantly on key variables, demonstrating that the group feeling more included tends to be more aged and tenured, hold a higher educational degree, work in the high-tech sector, and come from a developed area. Such a group also shows more engagement in their work but less exhaustion, feels that they have more opportunities for development, and gain more supports from colleagues and supervisors. Our findings point to the existence of subgroups of inclusion within the Chinese context and highlight the characteristics of these profiles, which in turn shed lights on how we can reach the goal of inclusion.